Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1016/j.xphs.2022.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Layer Deposition Processes Applied to Phage λ and a Phage-like Particle Platform Yield Thermostable, Single-Shot Vaccines

Abstract: Especially in developing countries, the impact of vaccines can be limited by logistical obstacles associated with multiple dose regimens, pathogen variants, and challenges imposed by requirements for maintaining vaccines at low temperatures during shipping and storage. Thus, there is a need for vaccines that can be flexibly modified to address evolving pathogen landscapes, are stable outside of narrow "cold-chain" temperatures and require administration of only single doses. Here we demonstrate in proof-of-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Herein, we demonstrate that λ PLPs (i) can be simultaneously decorated with trastuzumab and UbV.7.2 in rigorously defined surface densities, (ii) that the preparations are structurally and physically stable, and (iii) that the particles are homogeneous and amenable for pharmaceutical applications. Within this context, we recently demonstrated that antigen-decorated PLPs can be formulated in glassy powders that are stable and retain antigenicity for over 1 month at 50 °C, which is an important feature for a viable pharmaceutical preparation …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Herein, we demonstrate that λ PLPs (i) can be simultaneously decorated with trastuzumab and UbV.7.2 in rigorously defined surface densities, (ii) that the preparations are structurally and physically stable, and (iii) that the particles are homogeneous and amenable for pharmaceutical applications. Within this context, we recently demonstrated that antigen-decorated PLPs can be formulated in glassy powders that are stable and retain antigenicity for over 1 month at 50 °C, which is an important feature for a viable pharmaceutical preparation …”
Section: Discussionmentioning
confidence: 99%
“…Within this context, we recently demonstrated that antigen-decorated PLPs can be formulated in glassy powders that are stable and retain antigenicity for over 1 month at 50 °C, which is an important feature for a viable pharmaceutical preparation. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, the decorated particles are monodisperse, stable, and possess physiochemical properties amenable for pharmaceutical formulation and as required to address regulatory hurdles 53,63,64 . Indeed, we have recently demonstrated that antigen-decorated PLPs formulated in glassy dry powders are stable at 50 ˚C for more than one month 65 . Therefore, the lambda system described here allows for substantial flexibility and rigorous control in vaccine design and development, setting the stage for the construction of an "all-inone" vaccine platform.…”
Section: Introductionmentioning
confidence: 99%